2020
DOI: 10.1016/j.psj.2019.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Cobb 500 chick characteristics, bone ash, and residual yolk mineral reserves during time spent in the hatcher

Abstract: Previous work has identified an effect of hatch time on chick femur mineralization. This experiment assessed the impact of hatch time and a 24-h post-hatch unfed time period on chick bone mineralization and yolk mineral utilization. In early hatching chicks, yolk Mg, Zn, K, P, Fe, and Cu decreased by 40 to 50% over the 24-h post-hatch unfed time period, whereas yolk Ca and Na decreased by 25 to 40% ( P = 0.026). Yolk Sr was intermediate, decreasing by 37%. Late hatching chicks which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…( Sweeney, 1989 ) and the crude fat by modified Randall system, where the petroleum ether was evaporated at 105°C instead of 102°C using Velp Scientifica, SER 148 solvent extraction unit (Usmate Velate, Monza and Brianza, Lombarda, Italy) ( AOAC Official Method of Analysis, Method 2003.05 Method 2006, 2022 ) at Birling Avian Laboratories, Bringelly, Australia. The Ca and P content of the diets was determined at the University of New South Wales by inductively coupled plasma optical emission spectrometry ( ICP ) using a PerkinElmer OPTIMA 7300 (PerkinElmer Inc., Waltham, MA) following digestion with nitric acid and hydrogen peroxide as described by Hopcroft et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…( Sweeney, 1989 ) and the crude fat by modified Randall system, where the petroleum ether was evaporated at 105°C instead of 102°C using Velp Scientifica, SER 148 solvent extraction unit (Usmate Velate, Monza and Brianza, Lombarda, Italy) ( AOAC Official Method of Analysis, Method 2003.05 Method 2006, 2022 ) at Birling Avian Laboratories, Bringelly, Australia. The Ca and P content of the diets was determined at the University of New South Wales by inductively coupled plasma optical emission spectrometry ( ICP ) using a PerkinElmer OPTIMA 7300 (PerkinElmer Inc., Waltham, MA) following digestion with nitric acid and hydrogen peroxide as described by Hopcroft et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, starter diets are not specifically formulated for newly hatched chicks because requirements have been established considering the first 2 wk of rearing. After hatch, the chick depends on dietary nutrients for growth, but during the first days after hatch, there is an extra supply of Ca and very little supply of P from the residual yolk ( Yair and Uni, 2011 ; Hopcroft et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). Hopcroft et al. (2020) reported that at hatch, the Ca-to-P weight ratio in the yolk is as high as 2.9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps early fed broilers utilize the RY content differently compared to delayed fed broilers, without affecting the weight of the RY. For instance, it has been found that early fed chicks mainly utilized amino acids and minerals from the RY, whereas delayed fed chicks utilized lipids and moisture (Romanoff et al, 1944;Moran and Reinhart et al, 1980;Hopcroft et al, 2020). It can be speculated that chicks can also actively use the RY for development of the immune system, as the RY has been suggested to play a role in immune development (Murakami et al, 1992;Osama and Huwaida, 2013).…”
Section: Residual Yolkmentioning
confidence: 99%